Diabetes during Pregnancy: Influence of Body Mass Index on Composite Morbidity - O'Neil Dudley, Amy E.; Jenner, Zachary B.; Mendez-Figueroa, Hector; Ellis, Viviana S.; Chauhan, Suneet P. (American Journal of Perinatology Reports, 2017)
Objective This study aims to compare composite maternal and neonatal morbidities (MM, NM) among pregnant women with diabetes mellitus whose body mass index (BMI) at delivery was < 30 (group 1), 30.0 to 39.9 (group 2), and ≥ 40 kg/m2 (group 3). We hypothesized that increased BMI class at delivery would be associated with worsening maternal and neonatal outcomes.Methods This is a retrospective cohort study. MM was defined as: chorioamnionitis, wound infection, eclampsia, diabetic ketoacidosis, hypoglycemia admission, third/fourth degree laceration, and/or death. NM was defined as umbilical arterial pH < 7.0, 5 minute Apgar < 4, respiratory distress syndrome, mechanical ventilation, neonatal sepsis, stillbirth, and/or death. Odds ratios were adjusted for possible confounders.Results MM was noted in 8, 13, and 24% of groups 1, 2, and 3, respectively, and significantly more common in group 2 versus 1 (adjusted odds ratio [aOR]: 1.66) and group 3 versus 1 (aOR: 3.06). NM was noted in 7, 8, and 15% of each BMI group, respectively, and differed significantly between group 3 vs. 2 (aOR: 1.77).Conclusions The increased rate of morbidities between the BMI groups is useful to inform diabetic women and highlights the need for further investigation of diabetes and obesity as comorbidities in pregnancy.
Keywords: body mass index; composite maternal morbidity; composite neonatal morbidity; diabetes; obesity; pregnancy; MM; NM; BMI